EFFECT OF VARIOUS SOLVENTS ON THE EXTRACTION OF ANTIOXIDANTS FROM DRIED Basella alba LEAVES (Applied Biological Research, 2023)
Basella alba, an edible perennial vine, is an underutilized plant which  possesses many potential health benefits including antioxidant property.  Isolation of antioxidant compounds from the plant was attempted through  extraction with different solvents. The solvents of varying polarities, using  six extracting solvents (distilled water, ethyl acetate, hexane, ethanol,  methanol and acetone) were evaluated to assess the extraction of  antioxidant phenolics from dried leaves of B. alba. Each extract was  analyzed for total phenols, flavonoids and total antioxidant activity using 2- diphenyl-1-picrylhydrazyl radical scavenging activity assay (DPPH-RSA),  2,2azinobis, 3 ethyl benzothiazolin, 6-sulphonic acid assay (ABTS-RSA),  reducing power assay (RPA) and ferric reducing antioxidant power  (FRAP). Results revealed that methanol could extract maximum phenols  (779.58 mg GAE 100 g-1) while ethanol yielded maximum flavonoid (2726.43 mg RE 100 g-1) content. Methanol extract was found the most potent  scavenger of DPPH-RSA and ABTS-RSA (92.97 and 196.47 mg TE 100 g-1,  respectively) as well as depicted maximum RPA and FRAP values (2303.66  and 5.46 mg TE 100 g-1, respectively). Pearson correlation indicated a  positive significant relationship of total phenols and flavonoids with DPPH RSA, ABTS-RSA and RPA. FRAP revealing a strong correlation with  flavonoids. Overall, methanol was the most effective solvent for the  extraction of antioxidant phenolics from B. alba leaves and can be a useful  source of natural antioxidants.
Keywords: Antioxidants; Basella alba; solvents